Physics Micro Learning Video: Forming Pancasila Learner Profiles in Physics Learning - Bakri, Fauzi; Imtihani, Hajar; Muliyati, Dewi; Sumardani, Dadan (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
Pancasila learner profiles can be implemented in physics learning. This article publishes the results of research and development of physics learning videos. This physics learning video presents physics lessons that shape the Pancasila learner profile. Physics content is a wave that is presented contextually. This learning physics video use research and development of the Lee & Owens model. Product feasibility was assessed using a questionnaire by experts. The components assessed are the feasibility of the physics content, the feasibility of the learning process, the feasibility of the wave concept physics learning media in -learning videos. Sequentially get an assessment of 93.75%, 98.0%, 99.0%. The The implementation of the learning process on learning video products has facilitated the formation of Pancasila learner profiles. Overall, it can be concluded that the resulting physics learning video is very appropriate to be used to form a profile of Pancasila students.